JURIDICAL REVIEW MOTOR VEHICLE NOISE THRINGS IN INDONESIA'S POSITIVE LAW - Suparyo; Ardiansyah; Bagio Kadaryanto (International Peneliti Ekonomi, Sosial dan Teknologi, 2021)
As referred to in Article 106 paragraph (3) in conjunction with Article 48 paragraph (2) and paragraph (3) shall be sentenced to a maximum imprisonment of 1 (one) month or a maximum fine of Rp. 250,000.00 (two hundred and fifty thousand rupiah). As for the formulation of the problem in this study is HowMean Motor Vehicle Noise Threshold, HowJuridical Overview Motor Vehicle Noise Threshold, and HowLegal SettlementMotor Vehicle Noise Threshold in Indonesian Positive Law. The method used is normative legal research. Data sources consist of primary legal materials, secondary legal materials, and tertiary legal materials. In this study the data were analyzed qualitatively and in drawing conclusions the authors applied the method of deductive thinking. Based on the results of the study it is known thatMean Motor Vehicle Noise Threshold that is in the Regulation of the State Minister of the Environment Number 7 of 2009 concerning the New Type Motor Vehicle Noise Threshold. In the attachment of the Minister of Environment Regulation Noise Threshold confirms that the motorcycle noise threshold under 175cc is 80 dB and above 175cc is 83 dB.Juridical Overview Motor Vehicle Noise Threshold that in Article 285 of Law Number 22 of 2009 concerning Road Traffic and Transportation paragraph (1) that everyone who drives a Motorcycle on the Road that does not meet the technical and road-worthy requirements which includes rearview mirrors, horns , headlights, brake lights, directional lights, reflecting devices, speed measuring devices, exhaust, and tire groove depth as referred to in Article 106 paragraph (3) in conjunction with Article 48 paragraphs (2) and (3) shall be punished with imprisonment for a maximum of 1 (one) month or a maximum fine of Rp. 250,000.00 (two hundred and fifty thousand rupiah). Legal SettlementMotorized Vehicle Noise Threshold In Indonesian Positive Law that in taking action by law enforcement in this case the police and the Transportation Agency in carrying out enforcement in terms of noise testing, they never test how much noise is produced and law enforcers do not have the tools to measure the noise level generated from exhaust of motorized vehicle users on the highway.